Strategic Formulations and Financial Distress: Insights from Sales Growth and Profitability Ratios: Formulasi Strategis dan Kesulitan Keuangan: Wawasan dari Pertumbuhan Penjualan dan Rasio Profitabilitas - Prapanca, Detak; Kumalasari, Herlinda Maya (Universitas Muhammadiyah Sidoarjo, 2023)
This research looks into the complex relationship between sales growth, profitability ratios, and financial difficulty in businesses. It aims to provide practical recommendations to firm management for using sales growth and profitability data to identify and avoid financial crisis. Using a quantitative method, secondary data obtained from publicly traded companies' financial statements over a specific time period forms the basis of research. Multiple linear regression models are used to examine the relationship between sales growth and profitability ratios (the independent variables) and financial distress (the dependent variable). Statistical tests, such as ANOVA and t-tests, are used to assess the model's significance and regression coefficients. The findings show a significant relationship between sales growth, profitability ratios, and financial difficulty. Higher sales growth, in particular, is associated with an increased likelihood of financial trouble, as evidenced by the positive coefficient. Similarly, an increase in profitability ratios is linked to a higher probability of financial difficulty. This emphasizes the importance of sales growth and profitability ratios as signs of financial crisis. It is recommended that firm management closely monitor these indicators and include them into the company's financial risk management strategy in order to anticipate or mitigate possible financial difficulties. This study provides diverse stakeholders with critical insights and tools for efficiently understanding, identifying, and managing financial risks.